The Design of the E-Tracer Medical Record System in the Digital Era to Improve Health Data Management - Pramudita, Cindy Surya; Abdussalaam, Falaah; Sari, Irda (Transpublika Publisher, 2025)
The quality of healthcare facilities is greatly influenced by their health data management practices. To keep up with the times and provide better care in this digital era, healthcare organizations must swiftly adopt electronic technology. Creating and implementing a workflow system for electronic medical records is the focus of this article. With the principles of the Xtreme Programming development method, which can enhance health data management, the approach is based on rapid and efficient adjustments as well as continuous improvement. The author identifies that the hospital still relies on manual systems without the E-Tracer application, which could evaluate and identify an objective framework to measure and assess staff performance. This is useful in driving Continuous Quality Improvement (CQI) and other forms of sustainable quality enhancement. As a result, processes that should be running effectively within the data management workflow are instead lagging behind. Consequently, there is a gap between the organization's goals and staff performance, which has not fully met the established operational requirements. The goal of this study is to design and implement the E-Tracer medical record system to enhance health data management in the digital era. The findings suggest that hospitals could benefit from the performance evaluation capabilities of the E-Tracer system in terms of data management and staff performance. The quality of health data management can be measured by reviewing the reports generated by this system over a certain period of time. These reports can help with things like access control and avoiding breaches in medical data.